The White/Black Educational Gap, Stalled Progress, and the Long-Term Consequences of the Emergence of Crack Cocaine Markets - Evans, William N.; Garthwaite, Craig; Moore, Timothy J. (The Review of Economics and Statistics, 2016)
We propose the rise of crack cocaine markets as a key explanation for the end to the convergence in black-white educational outcomes in the United States that began in the mid-1980s. After constructing a measure to date the arrival of crack markets in cities and states, we show that the decline in educational outcomes for black males begins with the start of the crack epidemic. We also show that there are higher murder and incarceration rates after the arrival of crack cocaine and that these are predictive of lower black high school completion rates, a result consistent with human capital theory. We estimate that effects related to crack markets can account for approximately 40% to 70% of the fall in black male high school completion rates.